Epithelial-Mesenchymal Interactions for the Development of Intestinal Villi - Oh, Seunghoon (Dev Reprod, 2019)
Small intestine has a structure called villi that increases the mucosal surface area for nutrient absorption. Intricate and tight epithelial-mesenchymal interactions are required for villi development. These interactions are regulated by signaling molecules, physical forces, and epithelial deformation. Signaling molecules include hedgehog (Hh), bone morphogenetic protein (BMP) and Wnt ligands. The Hh ligand is expressed from the epithelium and binds to the underlying mesenchymal cells, resulting in aggregation into mesenchymal clusters. The clusters express BMP and Wnt ligands to control its size and spacing between clusters. The clusters then form villi. Despite the fact that the villi formation is studied extensively, we do not have a complete understanding. In addition, the recent study shows there is a great relationship between the overexpression of the Hh signal and development of cancer in the gastrointestinal tract. Therefore, signaling between epithelial and mesenchymal cells and their physical interactions will be discussed on this review.